Radar-guided mobile robot - Li, Jing (2015)
UGVs are very useful that it could be used for a board range of applications where human operators may be inconvenient, dangerous, or impossible to present. Recent growth of sensor technologies and expansion of microelectronics has greatly impacted the research and development of the UGV navigation system. Nowadays, an UGV is able to navigate, detect and operate automatically with optical sensors – camera or infrared. However, UGV with such optical sensors may fail to navigate in some special environment. In the final year project, the student has explored the possibility in using narrow band radar as the environment detecting system, which may operate well in the unfavorable environment for the optical sensors. The aim of the project is to refer to the existing prototype developed by two previous FYP students and improve the accuracy and stability of the system. The newly developed system was built on the Pioneer P3-AT robot with horn antenna as the radar system. The robot control system have been developed in MATLAB for the easy communication with radar processing system. The system was developed in a highly modularized manner for easy adoption in the future. A GUI dashboard was created such that the system could be used easily. For the radar navigation system, a “2-step” doorway detection procedure is proposed to perform indoor open doorway navigation. The experimental results give a detection error of around 14cm. The proposed doorway detection procedure is verified in 2 experiment sites. This study can be used as an initial step in the development of an inexpensive, multi-functional radar sensor for search-and-rescue missions to enhance the detection capability.